SYNTHESIS AND STUDY OF NEW METAL COMPLEXES DERIVED FROM 5-AMINO-3[4'-PNITRO PHENYL-THIOSEMICARBAZIDO]-1,2,4- THIADIAZOLE - Albaity, Sinan M M; Al-Obaidi, Najat J (Al-Nahrain Journal of Science, 2018)
The new ligand 5-amino -3-[4'-P-nitrophenyl thiosemicarbazido]-1,2,4-Thiodiazole(L) was prepared a long with its metal complexes with the selected ions Cr(III) ,Mn(II) ,Co(II), Ni(II), Cu(II) and Zn(II).The prepared complexes were elucidated by microelemental analysis (C.H.N.M), spectral methods (UV- vissible) and (FT.IR ),and other physical measurements (molar conductance in 10-3 M solution of (DMF), magnetic susceptibility for solid complexes and studied in solution using molar ratio(M:L) in ethanolic solution, Further more the stability of complexes in solutions were estimated via determination of stability constant Ks by spectrophotometric method.